L’ethnomusicologie française et le folk revival américain - Roger Mason (In Situ)
This paper focuses on an ethnomusicological field collection carried out by singer and musician Roger Mason in francophone Cajun Louisiana at the end of the 1960s. It illustrates how his methodology took into account certain attitudes of the French and American folk revival of the period, as well as the impact of sound technology and commercial recordings on his fieldwork. Finally, it discusses the consequences of this mission in France, with the organization of a tour by the Balfa Brothers that contributed to greater recognition of traditional Cajun music in academic circles and to a lasting popularization of the styles and repertoires.